2009
DOI: 10.1074/jbc.m109.047092
|View full text |Cite
|
Sign up to set email alerts
|

Direct Modification of the Proinflammatory Cytokine Macrophage Migration Inhibitory Factor by Dietary Isothiocyanates

Abstract: Isothiocyanates are a class of phytochemicals with widely reported anti-cancer and anti-inflammatory activity. However, knowledge of their activity at a molecular level is limited. The objective of this study was to identify biological targets of phenethyl isothiocyanate (PEITC) using an affinity purification approach. An analogue of PEITC was synthesized to enable conjugation to a solid-phase resin. The pleiotropic cytokine macrophage migration inhibitory factor (MIF) was the major protein captured from cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 51 publications
3
96
0
Order By: Relevance
“…Using a proteomics approach, we have discovered at least six protein targets of 8f other than Keap1, MIF, AKAP149, Prx3, Trx, HAT1, and KSRP. Inhibition of MIF, a well-established chemokine (46), has previously been associated with a derivative of sulforaphane, phenethyl isothiocyanate (47), and may be important in blocking inflammation. Modification of AKAP149 by 8f could influence protein kinase cell signaling, whereas modification of Prx3 and Trx could affect the antioxidant response.…”
Section: Discussionmentioning
confidence: 99%
“…Using a proteomics approach, we have discovered at least six protein targets of 8f other than Keap1, MIF, AKAP149, Prx3, Trx, HAT1, and KSRP. Inhibition of MIF, a well-established chemokine (46), has previously been associated with a derivative of sulforaphane, phenethyl isothiocyanate (47), and may be important in blocking inflammation. Modification of AKAP149 by 8f could influence protein kinase cell signaling, whereas modification of Prx3 and Trx could affect the antioxidant response.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Sulforaphane and other ITCs inactivate the tautomerase activity of MIF by reacting with a highly nucleophilic N-terminal proline residue in the active site of the enzyme. 41 Recent studies have demonstrated MIF tautomerase activity in human urine, and that oral administration of SF-rich broccoli sprout extracts to volunteers almost completely abolished this activity. 19 To our knowledge, urinary MIF tautomerase activity and the effects of SCI on urinary MIF activity have not previously been examined in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…52 Interestingly, studies from our group have shown that only catalytically active trimers undergo modification by these compounds at Pro1 in vitro and in the cell. 52,58 These studies highlight the reactivity of the N-terminal proline, Pro1, and provide a basis of novel strategies for specific detection and quantification of catalytically active MIF and targeting of its catalytic activities. The enrichment factor for the in silico protocol combining three parallel strategies was increased by a factor of 11.43 compared to the Maybridge experimental screening.…”
mentioning
confidence: 99%